Cooperative Resource Management in Cognitive Radio - Marojevic, V.; Reves, X.; Gelonch, A. (2007 IEEE International Conference on Communications, 2007)
Cognitive radio is generally understood as an intelligent wireless communication system aiming at the efficient utilization of radio resources. We argue for the extension of its scope to also address the management of computing resources, including processing and bandwidth capacities of SDR platforms, and present a cooperative resource management framework: The joint radio resource management (JRRM) and the computing resources management (CRM) entities interchange information to cooperatively decide if and what kind of terminal reconfiguration would be the most appropriate in each situation. Therefore, the cognitive radio system continuously observes the radio and the computing environments. We discuss a realistic case study and present a simple CRM algorithm. Simulation results show that such a cooperative resource management approach can achieve important improvements over the JRRM by itself. In particular, our proposal considerably reduces the number of lost user sessions due to inappropriate reconfiguration decisions and, thus, serves more wireless users.